Overview of garlic waste management, circular economy and upcycling - Heredia Martín, Juan Pablo (2025)
In the last three years, 2 billion tonnes of untreated and dismissed agricultural wastes have been accumulated without adequate management of reuse or final disposal, resulting in dumping or burning. The circular economy concept has gained increasing global recognition for addressing environmental and economic challenges. Garlic, the second most common bulb vegetable cultivated worldwide, generates significant waste during its industrial processing, including husks, stalks, straws, and leaves. These wastes, representing 3.0 to 3.7 million tonnes of residual biomass per year, are currently underutilised, with the usual treatment involving dumping in landfills or direct burning, leading to increased soil and air pollution. In this review, we aim to encourage innovation by presenting a search for state-of-the-art garlic waste management. We identified studies about garlic residual biomass valorisation as raw material for obtaining different extracts and polymers, even energy or biofuels. Finally, following circular economy principles, we propose potential uses for garlic by-products to be repurposed or upcycled as materials within agricultural or other production chains. The information above reveals an increasing demand and interest in garlic waste valorisation. Future studies are needed to exploit garlic by-products as important sources of biopolymers and phytochemicals.